Returns to education for women, assortative marriage matching, and home production - MYONG, Sunha (Institutional Knowledge at Singapore Management University, 2016)
I estimate returns to college education for women, accounting for how assortative marriage matching and the home production aﬀect labor supply and fertility choice, based on the National Longitudinal Study of Youth 1979 and the NLSY79 Child/Young Adults 1986—2012. First, the gain from home production, as measured by the average educational outcome of children, explains more than 80% of the total return. The direct impact of women’s college education on children’s outcome is much larger than the indirect eﬀect through the household income and time investment. Women’s college attainment rates would decrease by 8% without assortative marriage matching and by 17% without the direct impact on children’s educational attainment. Second, assortative marriage matching accounts for 21% of returns to college education for women with average characteristics. High-ability students beneﬁt more from the assortative marriage matching than low-ability students. For low-ability students, assortative marriage matching increases the inequality in college attainment rates by family backgrounds. Finally, women’s labor force participation rates would increase by 24% if the marginal productivity of household income on children’s outcome increases by 10%. As a comparison, if the wage structure of women were to be the same as men, the labor force participation rate would increase by 8%.